Chinese Food Security and Climate Change: Agriculture Futures - Ye L; Tang H; Wu, Wenliang; Yang P; Nelson, Gerald C.; Mason-D'Croz, Daniel; Palazzo, Amanda (ZBW - German National Library of Economics, 2014)
Climate change is now affecting agriculture and food production in every country of the world. Here the authors present the IMPACT model results on yield, production, and net trade of major crops in China, and on daily calorie availability as an overall indicator of food security under climate change scenarios and socio-economic pathways in 2050. The obtained results show a relatively optimistic outlook on yield, production and trade toward 2050. The outcomes of calorie availability suggest that China will be able to maintain a level of at least 3,000 kilocalories per day through 2010 to 2050. Overall, Chinese agriculture is relatively resilient to climate change. It is unlikely that Chinese food security by 2050 will be compromised in the context of climate change. The major challenge to food security, however, will rise from increasing demand coupled with regional disparities in adaptive capacity to climate change.